The philosophical discourse in the French romantic novel - Сипа, Лілія Михайлівна (The Journal of V. N. Karazin Kharkiv National University. Series “Philology”, 1970)
The article is devoted to the study of philosophical focus of the French novel of the Romantic period. It is stated that the philosophy is interpreted mainly as «the thinking by categories» in the Romantic period and the philosophical discourse is introduced mainly in the form of reflections in the artistic integrity of compositions. The functioning of reflections in the genre varities of French psychological novel («Oberman» by E.-P. de Senancour) and French personal novel («Lelia» by George Sand) is observed. The author’s translation of French citations is proposed.